2016
DOI: 10.1088/0963-0252/25/4/045015
|View full text |Cite
|
Sign up to set email alerts
|

Electron power absorption dynamics in capacitive radio frequency discharges driven by tailored voltage waveforms in CF4

Abstract: The power absorption dynamics of electrons and the electrical asymmetry effect in capacitive radio-frequency plasmas operated in CF 4 and driven by tailored voltage waveforms are investigated experimentally in combination with kinetic simulations. The driving voltage waveforms are generated as a superposition of multiple consecutive harmonics of the fundamental frequency of 13.56 MHz. Peaks/valleys and sawtooth waveforms are used to study the effects of amplitude and slope asymmetries of the driving voltage wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 98 publications
5
62
0
Order By: Relevance
“…More details of our model, tables and graphical representations of the cross sections can be found in Ref. 63. In the simulations we use 600 grid points to resolve properly the inter-electrode gap and between 15 000 and 30 000 time steps within an RF period, depending on the driving frequency, to resolve properly the temporal dynamics of all plasma species and to fulfill the relevant stability criteria of the numerical method.…”
Section: B Simulation Model and Methodsmentioning
confidence: 99%
“…More details of our model, tables and graphical representations of the cross sections can be found in Ref. 63. In the simulations we use 600 grid points to resolve properly the inter-electrode gap and between 15 000 and 30 000 time steps within an RF period, depending on the driving frequency, to resolve properly the temporal dynamics of all plasma species and to fulfill the relevant stability criteria of the numerical method.…”
Section: B Simulation Model and Methodsmentioning
confidence: 99%
“…Since the original study many investigations have demonstrated this effect through both simulation and experiment and extended it to the use of more than two frequencies to increase the amplitude asymmetry of the waveform [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. It has also been demonstrated that an electrical asymmetry can be generated using sawtooth-like waveforms where the rise and fall times of the voltage waveform differ [41][42][43][44][45][46][47][48]. In this case, the dc self-bias is generated as a result of a so-called slope asymmetry as opposed to the previously discussed amplitude asymmetry.…”
Section: Introductionmentioning
confidence: 97%
“…sheath expansion and collapse heating and γ-mode heating from secondary electron collisions 16 . Altering the shape of the applied voltage waveform affects these mechanisms directly as the phase-resolved sheath width mirrors the applied voltage amplitude 33,44,45 .…”
mentioning
confidence: 99%